Diskriminasi di Ruang Sekolah pada Film-Film Zainichi - Fatimah, Emma Rahmawati; Andayani, Santi; Muhfidah, Dewi; Almaghfiroh, Safina (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2023)
Japan's defeat in World War II did not necessarily become a complete liberation for the Korean zainichi. Japanese zainichi still feels discriminatory acts after Japan's colonization. The depiction of poverty and the living conditions of the zainichi who experience discrimination often colour the storylines of zainichi-themed films, including the Yakiniku Dragon, Go, and Pacchigi, objects of this research. Among the descriptions of the discrimination experienced by Zanichi, there is one similarity in the three films that is interesting to study further, the school setting, which is part of the storyline. The school became one of the spaces where discrimination against Korean zainichi took place. This study used the descriptive qualitative method. By using definition of discrimination in social perspective, this study discusses what forms of discrimination toward zainichi are reflected in three zainichi films, Pacchigi, Yakiniku Dragon and GO. The result shows some forms of discrimination toward zainichi. The forms of discrimination are physical violence, verbal violence and also social discrimination in the form of rejection and neglect from the majority group, namely Japanese society.